2021
DOI: 10.3389/fmolb.2021.692130
|View full text |Cite
|
Sign up to set email alerts
|

RNA m1A Methyltransferase TRMT6 Predicts Poorer Prognosis and Promotes Malignant Behavior in Glioma

Abstract: Background: Glioma is the most prevalent central nervous system tumor in humans, and its prognosis remains unsatisfactory due to a lack of effective therapeutic targets. The ectopic expression of N1-methyladenosine (m1A) regulators is a key participant in tumorigenesis and progression. However, the m1A regulator expression status, prognostic value, and relationship with tumor clinical features in glioma remain unclear.Methods: Public datasets were used to analyze the mRNA and protein expression levels of m1A r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 42 publications
5
40
0
Order By: Relevance
“…These results suggest that RNA modification writers affect the development of PCa mainly by participating in cell cycle regulation. This is consistent with the results of previous studies (Liu et al, 2020; Wang et al, 2020; Wang, Niu, et al, 2021). Further univariate and multivariate Cox analyses were performed for risk scores and clinical factors (age, stage and lymph node metastasis), indicating that the risk model of RNA modification writers might be an independent prognostic factor for PCa.…”
Section: Discussionsupporting
confidence: 94%
“…These results suggest that RNA modification writers affect the development of PCa mainly by participating in cell cycle regulation. This is consistent with the results of previous studies (Liu et al, 2020; Wang et al, 2020; Wang, Niu, et al, 2021). Further univariate and multivariate Cox analyses were performed for risk scores and clinical factors (age, stage and lymph node metastasis), indicating that the risk model of RNA modification writers might be an independent prognostic factor for PCa.…”
Section: Discussionsupporting
confidence: 94%
“…Recent research has shown that modi cation of m1A methylation plays an important role in the prognosis of OV and in shaping the immune microenvironment (34). TRMT6, a member of the tRNA methyltransferase family, is involved in post-translational modi cations, producing modi ed nucleoside m1A in tRNA, which acts as a writer (35). Zhao et al have shown that silencing TRMT6 inhibits cell proliferation, migration, and invasion in glioma (36).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have found positive associations with m 1 A regulators, such as the m 1 A methyltransferase TRMT6, and cancer ( Wang et al, 2019 ; Shi et al, 2020 ; Wang B. et al, 2021 ). However, few studies have established the biological mechanisms by which m 1 A regulators assert their oncogenic function.…”
Section: The Role Of M 1 a In Diverse Cellular Fun...mentioning
confidence: 99%
“…However, few studies have established the biological mechanisms by which m 1 A regulators assert their oncogenic function. Inhibition of Trmt6 resulted in decreased proliferation in glioma cell lines, establishing a potential oncogenic role for TRMT6 in regulating proliferation ( Macari et al, 2016 ; Wang B. et al, 2021 ). Furthermore, inhibition of Alkbh3 , an m 1 A demethylase, resulted in decreased proliferation in HeLa, PANC-1, and NSCLC cancer cells, suggesting a potential role for this demethylase in proliferation ( Tasaki et al, 2011 ; Ueda et al, 2017 ; Chen et al, 2019 ).…”
Section: The Role Of M 1 a In Diverse Cellular Fun...mentioning
confidence: 99%